High Biofilm-Forming Multidrug-Resistant Salmonella Infantis Strains from the Poultry Production Chain - Laura Musa; Valeria Toppi; Valentina Stefanetti; Noah Spata; Maria Cristina Rapi; Guido Grilli; Maria Filippa Addis; Giacomo Di Giacinto; Maria Pia Franciosini; Patrizia Casagrande Proietti (MDPI AG, 2024)
The ability of Salmonella species to adhere to surfaces and form biofilms, leading to persistent environmental reservoirs, might represent a direct link between environmental contamination and food processing contamination. The purpose of this study was to investigate the biofilm-forming ability of 80 multidrug-resistant (MDR) and extended-spectrum beta-lactamase (ESBL) producing Salmonella enterica serovar Infantis strains isolated from the broiler food chain production through whole genome sequencing (WGS), PCR, and morphotype association assays. Biofilm formation was quantified by testing the strains at two different temperatures, using 96-well polystyrene plates. The rough and dry colony (rdar) morphotype was assessed visually on Congo red agar (CRA) plates. Based on our results, all tested S. Infantis strains produced biofilm at 22 °C with an rdar morphotype, while at 37 °C, all the isolates tested negative, except one positive. Most isolates (58.75%) exhibited strong biofilm production, while 36.25% showed moderate production. Only 5 out of 80 (6.25%) were weak biofilm producers. WGS analysis showed the presence of the fim cluster (fimADF) and the csg cluster (csgBAC and csgDEFG), also described in S. Typhimurium, which are responsible for fimbriae production. PCR demonstrated the presence of csgD, csgB, and fimA in all 80 S. Infantis strains. To our knowledge, this is the first study comparing the effects of two different temperatures on the biofilm formation capacity of ESBL producing S. Infantis from the broiler production chain. This study highlights that the initial biofilm components, such as curli and cellulose, are specifically expressed at lower temperatures. It is important to emphasize that within the broiler farm, the environmental temperature ranges between 18-22 °C, which is the optimum temperature for in vitro biofilm formation by Salmonella spp. This temperature range facilitates the expression of biofilm-associated genes, contributing to the persistence of S. Infantis in the environment. This complicates biosecurity measures and makes disinfection protocols on the farm and in the production chain more difficult, posing serious public health concerns.